(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The idea of this project comes into the picture from various uses of sensors that are present in our surroundings. So, we can actually play with them by using two or more sensor mechanisms that end up as new inventions. Therefore, we are keen to look forward to one of the highly scoped and well-furnished sensors i.e., Gyroscope Sensor with an element of Light Sensor. This sensor is capable of measuring the orientation of the body and the angular velocity of the object. In our android project, we embedded the flashlight feature in the Gyro sensor’s angle alteration logic. This mechanism successfully leads to the flashlight of the camera getting ON & OFF when the device is tilted or shifted along the reference angle. This collaboration of sensors plays an important role for a device that does not have that feature